Isolation and molecular identification of cutaneous leishmaniasis in humans and dogs in middle Euphrates, Iraq - Haider H. Alseady; Sahad M. Al-Dabbagh (Iraqi Journal of Veterinary Sciences)
In Iraq, one of the endemic illnesses is cutaneous Leishmaniasis. This study aimed to characterize local isolates of Leishmania tropica and Leishmania major molecularly and determine how closely related they were to reference isolates from nearby nations. A total of 140 and 60 skin lesion samples were collected from patients and dogs, respectively, from September 2021 to March 2022; molecular methods carried out to achieve the prevalence of cutaneous Leishmaniasis in humans and dogs, Nested PCR was done using the kDNA gene for phylogenetic analyses. The overall prevalence of cutaneous Leishmaniasis was 35% and 88.33% in humans and dogs, respectively; the findings showed the total prevalence of Leishmania major significant in dogs was 71.69% compared to Leishmania tropica was 28.35% with significant differences. Fifteen positive samples (Ten human and five dogs) were sequencing to Gen-bank database for phylogenetic analyses, which detected that seven of local isolates skin lesion human samples belongs to Leishmania major isolates IQ Kut isolates, Iraq and three isolates belongs to Leishmania tropica isolates IQ3, Iraq. Four of the local isolates skin lesion dog samples belong to Leishmania major isolates IQ Kut, Iraq, and one isolate belong to Leishmania tropica isolates IQ-7 Iraq. Determining many Leishmania major in humans and dogs indicates that dogs are key parasite reservoirs and significant zoonotic contributes to disease transmission to humans in the Middle Euphrates, Iraq.